Stress management in South Africa - D. J.W. Strümpfer (South African Journal of Business Management, 1985)
A distinction is made between eustress and distress, and the complexity of stress phenomena is emphasized. Acceptance of corporate social responsibility is posed as the most fundamental form of stress management at the social and community level. Sound management practices are viewed as basic to health-enhancing organizations. Occupational differences are highlighted. Stress management training is discussed in terms of who needs training, individual vs. group approaches, and objectives. Knowledge acquisition and self-assessment are introduced. Brief discussions of specific skills training follow: Relaxation, physical exercise, rational-emotive thinking, goal setting, time management, personal and career development counselling, and preventive health management. Lastly, employee counselling programmes are mentioned. The role of follow-up evaluation is emphasized.
Keywords: 650